W poszukiwaniu autentyczności - Błaszczyk, Marek (Człowiek i Społeczeństwo, 2025)
Recenzja książki: Stefan Szary, Być sobą. Autorefleksja terapeutyczna, Wydawnictwo von Borowiecky, Warszawa 2023 The article presents a critical approach to Być sobą. Autorefleksja terapeutyczna by Stefan Szary (Wydawnictwo von Borowiecky, Warszawa 2023). It discusses the main theses presented in the dissertation and invites to reflection on authenticity and the place and role of man in the world.